TUBERCULOSIS VERSUS VASCULITIS - Baig, Zahid Farooq; Raja, Khalid Mahmood; Abbas, Fahad (Journal of Ayub Medical College Abbottabad, 2014)
Vasculitis (Wegeners Granulomatosis and Microscopic Polyangiitis) and Tuberculosis share many features including constitutional symptoms and respiratory tract involvement. The presence of kidney involvement with new onset azotaemia and active urine sediment support the diagnosis of vasculitis. We describe two cases that were diagnosed to be suffering from tuberculosis and placed on anti-tuberculosis therapy. On further workup they were found to be suffering from pauci-immune glomerulonephritis and recovered well with treatment. Keywords: Tuberculosis, Microscopic polyangiitis, Wegener's granulomatosis, ANCA-associated vasculitis